Les Pays de Maghrebe et la question Palestinienne - Gueriniai, Garadi (Sciences humaines; Vol. 30 (2013): SCIENCES HUMAINES, 2014)
Through a reading of the history of inter-Arab policies, including the Palestinian question, of the Maghreb countries, we are asked to understand on what basis the Maghreb countries have reacted in a certain way.   The treatment of this central question of our research led us to see two kind of policies: one tries to couple between the interest on one side, while maintaining relations with Israel, because we know that to be clearly seen to eyes of Westerners in general and Americans in particular need to be normalized with the Jewish state, or at worst, do not be bitter against him, and solidarity with the Palestinians on the other side. However, this kind of behavior is unsustainable as both party in question are opposed, leading the partisans of this policy to cover up their contacts with the Israelis. That’s why we have difficulty to understanding certain policies  and behaviors.    The second policy is based on solidarity, without giving importance to the interest.  Finally, inter-Arab  solidarity  between  the Maghreb and the rest of the Arab world in general and the Palestinian question in particular, has been marked by the permanent crisis of inter-Arab  political  system. In the Maghreb, the political question of the Saharan conflict has become a major obstacle to starting a project unit and a common foreign policy. Political realism  and  economic  pragmatism became the refrain of the new discourse of leaders of the Maghreb.